Glacial Stratigraphy of the Bulkley River Region: A Depositional Framework for the Late Pleistocene in Central British Columbia - Stumpf, Andrew; Broster, Bruce; Levson, Victor (Géographie physique et Quaternaire, 2004)
AbstractA depositional framework for late Pleistocene sediments in central British Columbia was developed from the composite stratigraphy of glacial sediments found in the Bulkley River region. Nonglacial deposits correlated to the Olympia Nonglacial Interval, are overlain in succession by sub-till, ice-advance sediments, Late Wisconsinan (Fraser Glaciation) till, and late-glacial sediments. Due to local erosion and depositional variability, some of the units are not continuous throughout the region and differ locally in their thickness and complexity. At the onset of the Fraser Glaciation, ice advance was marked by rising base levels in rivers, lake ponding, and ice marginal subaqueous deposition. Physiography and glacier dynamics influenced the position of drainage outlets, direction of water flow, and ponding. The region was completely ice covered during this glaciation and ice-flow directions were variable, being dominantly influenced by the migrating position of ice divides. Deglaciation was marked by the widespread deposition of fine-grained sediments in proglacial lakes and glaciofluvial sands and gravels at locations with unrestricted drainage.